Implementasi Teori Nasikh-Mansukh dalam Penetapan Hukum Fikih - Pratiwi, Rindy Nadya; Habibulloh, Muh. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Islamic legal thought developed in line with the process of the revelation of Allah which did not come down all at once. Nasikh and Mansukh's theories are two things that refer to a method for eliminating, canceling and replacing laws in Islamic law. Nasikh is the cancellation, revocation, or legal replacement of the previous proposition to the next, newer proposition by adapting to the conditions at that time. Meanwhile, Mansukh is a proposition that is revoked, canceled or replaced by the new law. To explore the law in formulating fiqh provisions, you need to be able to understand the concept of nasikh-mansukh, because if you don't understand the concept correctly, it can lead to things that are not true. In terms of confirming jurisprudential law, the Nasakh-Mansukh theory has the right place as a scientific tool that can be used as a basis for establishing laws carefully, in accordance with developments, and based on valid arguments. This research uses library research methods with a qualitative approach. Data was obtained from scientific journals, books and scientific articles discussing Nasikh and Mansukh as well as fiqh studies. All data was analyzed using thematic analysis techniques by exploring, studying and analyzing references and figures' thoughts.